Long-term outcomes of liver transplantation for biliary atresia and results of policy changes: over 20 years of follow-up experience - Kwon, Yiyoung; Ahn, Yoon Ji; Yang, Jaehun; Kim, Eun Sil; Choe, Yon Ho; Lee, Sanghoon; Kim, Mi Jin (Frontiers in Pediatrics, 2024)
Objective Biliary atresia (BA) patients develop chronic liver disease after the Kasai operation and are eventually indicated for liver transplantation (LT). The purposes of this study were to analyze long-term outcomes after LT and risk factors that affect complications to reduce graft failure. Study design Overall, 145 pediatric patients who underwent LT between June 1996 and June 2020 after a diagnosis of BA were included. We performed a retrospective analysis of medical records and evaluated patient and graft survival, cumulative incidence of complications, risk factors, and the results of policy changes. Results Patient and graft survival rates in over 20 years were 95.8% and 91.0%, respectively. Post-transplantation lymphoproliferative disease was frequently observed in the early period of immunosuppression within the first 1–2 years after LT. The incidence of cholangitis and rejection steadily increased over time. Weight-to-portal vein size was evaluated as a risk factor for cholangitis and bile duct strictures (OR = 12.82, p = 0.006 and OR = 16.54, p = 0.015, respectively). When evaluated using 2013 as a reference point, the split graft indication was expanded and the group that received LT after 2013 had a significantly lower survival over time compared with that of the group that received LT before 2013 (p = 0.006). Conclusion This study revealed time differences in prevalence of complications. The evaluation of weight-to-duct or vessel size is a more important factor in considering complications than the graft-to-recipient weight ratio. Survival outcomes may have been altered by a policy change that affects the donor type ratio in transplantation.